Insight into aquaculture's potential of marine annelid worms and ecological concerns: a review. (2nd November 2018) - Pombo, Ana; Baptista, Teresa; Granada, Luana; Ferreira, Susana M. F.; Gonçalves, Sílvia C.; Anjos, Catarina; Sá, Erica; Chainho, Paula; Cancela da Fonseca, Luís; Fidalgo e Costa, Pedro; Costa, José L.
Abstract: Polychaetes are marine annelid worms that can contribute to aquaculture diversification. Its culture has been viable, and commercially attempted, but intensive production has progressed only in few countries around the world. In the countries with no production, marine polychaetes are imported or harvested. A strong and sustained research investment provided to a better understanding of the nutritional requirements and reproduction of some species. Recent studies showed new technical improvements, which can lead to an important progress in productivity and give a new impetus to the polychaete production. Some marine worm species were identified as good candidates for integrated multitrophic aquaculture. The development of cost‐effective aquaculture techniques for marine annelid worms is essential to ensure a balance between commercial interests and the preservation of ecosystems. The influence of polychaete aquaculture on the environment and vice versa raise important concerns related to ecological security and sustainability of this activity. This review focus on the main technical improvements and advances that have been made in areas as diverse as: aquaculture potential of polychaetes, reared species, main species used worldwide, and highlights biological and ecological concerns, important challenges and recommendations.